Sport-specific video-based reactive agility training in rugby union players - Engelbrecht, L.; Welman, K. E.; Terblanche, E. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
In rugby union, players are constantly faced with a dynamic environment. Hence successful play requires a quick and accurate interpretation and response to these changing situations. Evasive reactive agility (RA) manoeuvres could lead to successful tackle breaks and advancing beyond the advantage line. More so RA can distinguish between higher and lesser skilled athletes (Wheeler et al.,2010). Purpose The study set out to investigate the effectiveness of a sport-specific video-based RA training programme for rugby union players in comparison to a field-based training programme. Methods: 26 male rugby union players (18-24 years) participated in the study and were randomly divided into video-training (VT), field-training (FT) or control (C) groups. VT sessions included viewing and physically reacting to rugby attacking scenarios displayed on a 2.0m x 1.5m screen. FT sessions consisted of drills that included decisionmaking scenarios and mini-games. The players completed a 6 week intervention programme of 2 sessions per week. Anthropometrical measurements (height, body mass, % body fat, % lean body mass), linear speed, change of direction speed and RA, were assessed pre and post intervention and after 6 weeks to assess retention. Results: Both VT and FT improved RA compared to C, with differences in the training effect of 13% (+6) and 17% (+4), respectively (p<0.01). FT is possibly better than VT to improve RA (3+4%). Both training interventions were able to maintain its improvements in RA following the retention period. Discussion VT and FT produced significant improvements in RA performance of rugby union players. These changes were also significantly greater than with rugby training alone (C), indicating that short-term exposure to RA training may lead to improved RA performance. The improvements seen in the VT group was in accordance to the results of Serpell et al. (2011). The inclusion of mini-games in the FT group may have exposed the players to more decision-making scenarios than in VT, which may explain the slightly greater gains in RA in the FT group. Gabbett (2006) also found that skill-based conditioning games significantly improved rugby league players` attacking ability, which may be due to increased ability to read patterns of play. Conclusion: VT and FT are valid sport-specific methods for conditioning RA in rugby union players. VT can be used as an effective alternative conditioning method or add-on to improve RA in rugby union.